Board affiliation and pay gap - Shenglan Chen; Hui Ma; Bu Danlu (China Journal of Accounting Research, 2014)
This paper examines the effects of board affiliation on the corporate pay gap. Using a sample of Chinese listed firms from 2005 to 2011, we find that boards with a greater presence of directors appointed by block shareholders have lower pay gaps. Furthermore, the governance effects of board affiliation with and without pay are distinguished. The empirical results show that board affiliation without pay is negatively related to the pay gap, while board affiliation with pay is positively related to the pay gap. Overall, the results shed light on how block shareholders affect their companies' pay gaps through board affiliation.
Keywords: G34; J33; M12; 650; Board affiliation; Pay gap; Agency problem